Development of large-scale urban parks for tourism and recreation : the case of Sentosa, Singapore. - Kee, Shufen. (2008)
This study highlights the development of Sentosa from 1968 to 2002 as well as evaluates its successes and failures. The analysis is based on the various phases characterised by the major developmental change during that time period.